2019
DOI: 10.1142/s0219877019500378
|View full text |Cite
|
Sign up to set email alerts
|

Customer’s Intention to Adopt Mobile Banking Services: The Moderating Influence of Demographic Factors

Abstract: The variance in users’ characteristics, according to demographic factors, is crucial in segmenting retail banking customers and making marketing decisions. Therefore, the effects of these factors should be examined to help IT providers enhance m-banking services. This study seeks to build a conceptual model that determines the moderating influence of demographic factors on the customer’s intention to adopt m-banking. A questionnaire was distributed in Saudi Arabia and the responses were analyzed through a stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…The final determinant in the research model is awareness. Although awareness was considered in the acceptance of m-banking [22], we believe it would be significant in enrolling in online courses. The proposed model considers five moderators: college, college level, an internet connection, a personal computer ownership, and involvement in online courses.…”
Section: The Research Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The final determinant in the research model is awareness. Although awareness was considered in the acceptance of m-banking [22], we believe it would be significant in enrolling in online courses. The proposed model considers five moderators: college, college level, an internet connection, a personal computer ownership, and involvement in online courses.…”
Section: The Research Modelmentioning
confidence: 99%
“…Experience with using information technology is how much time the user spends using the technology [12,20,22]. In this study, experience is divided into two sets: computer literacy (EXP CL) and Technical Knowledge (EXP2).…”
Section: The Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we argue that if students perceived the use of Moodle needs less effort and is not difficult, they will form a positive attitude towards the systems and they perceive the use of this LMS as useful for their academic performance (Davis, 1989). Many studies have found significant positive effect of effort expectancy on performance expectancy (e.g., Alalwan et al, 2016Alalwan et al, , 2017Alalwan et al, , 2018Alkhaldi & Kharma, 2019;Alshurideh et al, 2020;Jaradat & Al Rababaa, 2013;Joo et al, 2016;Rabaai et al, 2015), and on attitude (e.g., Abdullah & Ward, 2016;Davis, 1989;Sabah, 2019;Wu & Chen, 2017). Consequently, this study posited the following hypotheses: H9: Effort expectancy significantly influences performance expectancy.…”
Section: Effort Expectancy (Ee)mentioning
confidence: 94%
“…The demographic characteristics of users' online banking service are important because it is related to market segmentations as one of the bank's strategies to retain its customers (Alkhaldi & Kharma, 2019). According to several previous surveys, the percentage of internet banking users are not as many as the percentage of mobile banking users.…”
Section: Introductionmentioning
confidence: 99%